Efficacy and Safety of Anti-PD-1/ PD-L1 Monotherapy for Metastatic Breast Cancer: Clinical Evidence - Qi, Yihang; Zhang, Lin; Wang, Zhongzhao; Kong, Xiangyi; Zhai, Jie; Fang, Yi; Wang, Jing (Frontiers in Pharmacology, 2021)
Background: Success has been reported in PD-1/PD-L1 blockade via pembrolizumab, atezolizumab or avelumab monotherapy in manifold malignancies including metastatic breast cancer. Due to lack of large-scale study, here we present interim analyses to evaluate the safety and efficacy of this promising strategies in patients with advanced breast cancer. Methods: Six studies including 586 advanced breast cancer patients treated with anti-PD-1/PD-L1 monotherapy agents before July 1, 2020 were included. The anti-PD-1/PD-L1 agents include pembrolizumab, atezolizumab land avelumab. Statistics was analyzed by R software and IBM SPSS Statistics 22. Results: Global analysis showed that for this monotherapy, the complete response (CR) was 1.26%, partial response (PR) was 7.65%, objective response rate (ORR) was 9.85% and disease control rate (DCR) was 18.33%. 1-year overall survival rate and 6-months progression-free survival rate were 43.34% and 17.24%. Overall incidence of adverse events (AEs) was 64.18% in any grade and 12.94% in severe grade, while the incidence of immune-related AEs (irAEs) was approximately 14.75%: the most common treatment-related AEs of any grade that occurred in at least 5% of patients were arthraigia and asthenia; the most common severe treatment-related AEs occurred in at least 1% of patients were anemia and autoimmune hepatitis; the most common irAEs were hypothyroidism. Besides, the incidence of discontinue and death due to treatment-related AEs was about 3.06% and 0.31%. Additionally, by comparing efficacy indicators between PD-L1-positive and PD-L1-negative groups, an implicated correspondence between efficacy and the expression of PD-L1 biomarker was found: the PR was 9.93% vs 2.69%; the ORR was 10.62% vs 3.07%; the DCR was 17.95% vs 4.71%. Conclusion: Anti-PD-1/PD-L1 monotherapy showed a manageable safety profile and had a promising and durable anti-tumor efficacy in metastatic breast cancer patients. Higher PD-L1 expression may be closely correlated to a better clinical efficacy.